In-depth investigation of metallization aging in power MOSFETs. Issue 9 (August 2015) - Ruffilli, R.; Berkani, M.; Dupuy, P.; Lefebvre, S.; Weber, Y.; Legros, M.
Abstract: The long-term reliability of modern power MOSFETs is assessed through accelerated electro-thermal aging tests. Previous studies have shown that the source metallization (top metal and wires) is a failure-prone location of the component. To study how the top aluminum metallization microstructure ages, we have performed ion and electron microscopy and mapped the grain structure before and after avalanche and short-circuit aging tests. The situation under the bond wires is significantly different as the bonding process induces plastic deformation prior to aging. Ion microscopy seems to show two inverse tendencies: grain growth under the wires and grain refinement elsewhere in the metallization. Transmission electron microscopy shows that the situation is more complex. Rearrangement of the initial defect and grain structure happen below and away from the wire. The most harmful fatigue cracks propagate parallel to the wire/metal bonding interface. Highlights: Evolution of the microstructure of a MOSFET Al-based metallization during aging Evolution of wire bonding/metallization interface and structure before and after aging Grain orientation mapping using two different techniques Aging mechanism through diffusion based crack propagation revealed